On the Determinants of Global Bilateral Migration Flows - Jesus Crespo Cuaresma; Mathias Moser; Anna Raggl (WWWforEurope, 2013)
We present a method aimed at estimating global bilateral migration flows and assessing their determinants. We employ that fact that available net migration figures for a country are (nonlinear) aggregates of migration flows from and to all other countries of the world in order to construct a statistical model that links the determinants of (unobserved) migration flows to total net migration. Using simple specifications based on the gravity model for international migration, we find that migration flows can be explained by standard gravity model variables such as GDP differences, distance or bilateral population. The usefulness of such models is exemplified by combining estimated specications with population and GDP projections in order to assess quantitatively the expected changes in migration flows to Europe in the coming decades.
Keywords: F22; O15; J11; 330; bilateral migration flows; gravity model; nonlinearly aggregated models